A New Therapeutic Candidate for Cardiovascular Diseases: Berberine - Cai, Yun; Xin, Qiqi; Lu, Jinjin; Miao, Yu; Lin, Qian; Cong, Weihong; Chen, Keji (Frontiers in Pharmacology, 2021)
Cardiovascular diseases (CVD) are the leading cause of death in the world. However, due to the limited effectiveness and potential adverse effects of current treatments, the long-term prognosis of CVD patients is still discouraging. In recent years, several studies have found that berberine (BBR) has broad application prospects in the prevention and treatment of CVD. Due to its effectiveness and safety for gastroenteritis and diarrhea caused by bacterial infections, BBR has been widely used in China and other Asian countries since the middle of the last century. The development of pharmacology also provides evidence for the multi-targets of BBR in treating CVD. Researches on CVD, such as arrhythmia, atherosclerosis, dyslipidemia, hypertension, ischemic heart disease, myocarditis and cardiomyopathy, heart failure, etc., revealed the cardiovascular protective mechanisms of BBR. This review systematically summarizes the pharmacological research progress of BBR in the treatment of CVD in recent years, confirming that BBR is a promising therapeutic option for CVD.